Hypothetical study of small hive beetle aethina tumida infestation in honeybees, risk commodities and probabilities for its introduction in türkiye - Ahmet Onur GİRİŞGİN; Levent AYDIN; Yunus Emre YÖRÜK (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2022)
Türkiye is the second-largest honey producer globally; however, the export of honey and bee products does not adequately support the beekeeping industry. Pests account for the largest share of expenditure for agents found in honeybees in the country. Although the Small Hive Beetle (SHB) has not been detected in Türkiye, a risk assessment was performed to determine what happens if it enters the country. The risk assessment included: a) hazard identification; b) risk pathway determination; c) risk assessment for entry via the identified pathways; and d) outcome assessment for becoming endemic in Türkiye. The Risk AMP add-in program was used to assess the probability of distribution for each method of entry, pathway, and simulation. According to the simulations, the probability of SHB introduction in Türkiye varies from 0.17 per 1000 events/days (1.7 per 10000 days or 27 years) to 0.6 per 1000 events/imports (6 per 10000 days or 27 years). The highest likelihood of introduction comes from fruit import (11/15) and soil/compost import (4/15). The mean probability of introducing SHB infestation after 1000 iterations of the constructed model is 0.37 per 1000 events/days (3.7 within 10000 days or 27 years). Finally, the simulated average cost of SHB after the possible introduction is 523 million US $ for Türkiye. With these simulated data, risk assessment of a non-detected pest, SHB, was determined for Türkiye.